Lipid Assemblies as Tools for Drug Delivery - Gupta, Anju (International Journal of Lipids, 2020)
This review discusses lipid assemblies—from liposomes to solid lipid nanoparticles—as platforms for drug delivery. It covers design principles, targeting strategies, and manufacturing considerations.
Keywords: Lipid Assemblies; Liposomes; Solid Lipid Nanoparticles; Drug Delivery; Targeting Strategies